A federalist's dilemma: Trade-offs between social legitimacy and budget responsibility in multi-tiered welfare states. (February 2019) - Bonoli, Giuliano; Natili, Marcello; Trein, Philipp
In multi-tiered states, subnational policymakers face a dilemma: on one hand, they must ensure the social legitimacy of their subnational unit by owning relevant policies including their potentially negative consequences; on the other, they have to manage their budget responsibly, which limits the scope of policy development. We study this dilemma in relation to social policies, by examining how the constituent units and municipalities in Germany, Italy, Spain and Switzerland deal with it, taking social assistance as an empirical example. Our analysis suggests that the combination of the federation's history and a multinational political context affects the incentives and the choices made by the policymakers regarding ownership and disownership of policy competencies in the field of social assistance. By analysing mechanisms that are likely to play out in multi-tiered welfare states, our article contributes to both the social policy and the political science literatures.